Doctor–patient communication in a Southeast Asian setting: the conflict between ideal and reality - Claramita, Mora (Springer Netherlands, 2010)
Doctor–patient communication has been extensively studied in non-Western contexts and in relation to patients’ cultural and education backgrounds. This study explores the perceived ideal communication style for doctor–patient consultations and the reality of actual practice in a Southeast Asian context. We conducted the study in a teaching hospital in Indonesia, using a qualitative and a quantitative design. In-depth interviews were conducted with ten internal medicine specialists, ten internal medicine residents, 16 patients in two groups based on education level and ten most senior medical students. The contributions of doctors and patients to the communication during consultations were observed and rated quantitatively by thirty internal medicine residents, 393 patients with different educational backgrounds and ten senior medical students. The ‘informed and shared decision making’ is the central observation in this quantitative study. The results of the interviews showed that Southeast Asian stakeholders are in favor of a partnership style of communication and revealed barriers to achieving this: doctors and patients are not prepared for a participatory style and high patient load due to an inefficient health care system does not allow sufficient time for this type of communication. The results of the quantitative study showed a sharp contrast between observed and ideal communication styles. A paternalistic style seems to prevail, irrespective of patients’ educational background. We found a sharp conflict between ideal and reality concerning doctor–patient communication in a Southeast Asian context. Further studies should examine ways to change the prevailing communication style in the desired direction.